Potential of histone deacetylase inhibitors in the control and regulation of prostate, breast and ovarian cancer - Pramanik, Siddhartha Das; Kumar Halder, Amit; Mukherjee, Ushmita; Kumar, Dharmendra; Dey, Yadu Nandan; R, Mogana (Frontiers in Chemistry, 2022)
Histone deacetylases (HDAC) are enzymes that play a role in chromatin remodeling and epigenetics. They belong to a specific category of enzymes that eliminate the acetyl part of the histones' -N-acetyl lysine, causing the histones to be wrapped compactly around DNA. Numerous biological processes rely on HDAC, including cell proliferation and differentiation, angiogenesis, metastasis, gene regulation, and transcription. Epigenetic changes, specifically increased expression and activity of HDAC, are commonly detected in cancer. As a result, HDAC inhibitors could be used to develop anticancer drugs. Although preclinical outcomes with HDAC as monotherapy have been promising clinical trials have had mixed results and limited success. In both preclinical and clinical trials, however, combination therapy with different anticancer medicines has proved to have synergistic effects. Furthermore, these combinations improved efficacy, decreased tumor resistance to therapy, and decreased toxicity. In the present review, the detailed modes of action, classification of HDAC, and their correlation with different cancers like prostate, breast, and ovarian cancer were discussed. Further, the different cell signaling pathways and the structure-activity relationship and pharmaco-toxicological properties of the HDAC inhibitors, and their synergistic effects with other anticancer drugs observed in recent preclinical and clinical studies used in combination therapy were discussed for prostate, breast, and ovarian cancer treatment.